Blood Parameters of Lactating Cows Fed Calcium Salts as Energetic Source - Martins, William Del Conte; Cunha, Sérgio Henrique Mioso; Boscarato, André Giarola; de Lima, Jonathan Soares; Esteves Junior, Jair Dario; Uliana, Gian Luca Todero; Pedrini, Mateus Trindade; Alberton, Luiz Romulo (Acta Scientiae Veterinariae, 2018)
Background: The negative energetic balance of lactating cows that occurs during the few weeks postpartum shifts the hormonal profile of the animal. These alterations may lead to metabolic disturbance as ketosis and lipid infiltration. Hypocalcemia is another metabolic problem that occurs in the peripartum period, it is characterized by the reduction in blood levels of calcium (Ca2+) near birth. Blood parameters illustrates the nutritional status of milking cows. The serum levels of glucose, β-hydroxybutyrate (BHB) and cholesterol are parameters that reveal liver condition and it is very important for the metabolism of milking cows. The objective of this study was to evaluate three additives in the form of a calcium salts on blood parameters of lactating cows. Materials, Methods & Results: Two Latin square 4x4 were used, whereas one comprehended of early lactation cows and the other of mid lactation cows. Animals of 2nd and 3rd parity were used only. Parity was distributed evenly among groups. The trial consisted of 4 groups with 4 treatments as follow: T1: 300 g of calcium acetate, T2: 200 g of calcium propionate, T3: 200 g of calcium salts of fatty acids, and T4: control without any calcium additive. Blood samples were collected for analysis of serial calcium, glucose, β-hydroxybutyrate (BHBA) and cholesterol. The calcium levels were higher in T1 than T3 in early lactation. There was no significant difference of glucose levels between groups. Groups T1 and T2 had lower amounts of BHBA. Cholesterol was higher in T3 and T1 in the early lactation and just in T3 was higher in the mid lactation. Discussion: Adjust the Ca2+ flow due to high feed consumption and milk production near birth is a big challenge for milking cows due to the difficulties to maintain normal serial levels of Ca2+ in the early lactation. The lower serial levels of Ca2+ in the group supplemented with calcium salts of fatty acids is due to its physical characteristics that reduces its effects on ruminal microbiota and also reduced absorption of fatty acids in intestine. The evaluation of total cholesterol can be a parameter to judge the productive capacity of milking cows, because it demonstrates the capacity of corporal fat mobilization and ingestion of energy to produce milk. An increase of total cholesterol in cows supplemented with calcium salts of fatty acids is justified by the higher intake of fatty acids in the feed containing fat, which leads to a greater lipid metabolism in blood. As the literature has limited information about calcium acetate, it is believed that the animals supplemented with calcium acetate showed higher levels of cholesterol because the acetate is converted to Acetyl coenzime A, it is the basis for cholesterol biosynthesis in lactating cows. The BHBA can be considered as an indicator of negative energetic balance due to its correlation between energetic demand and energy reserves. As propionate is produced by ruminal fermentation and is the principal source for gluconeogenesis in peripartum cows, it lowered level of BHBA in the propionate supplemented group. The acetate availability is fundamental to attend the energetic requirements of lactating cows. The acetate enters in the synthesis of fatty acids as Acetyl coenzyme-A or enters in Krebs cycle through condensation with oxaloacetate, this explains the lower serial levels of BHB in group T1. It was concluded that T1 and T2 lowered the values of BHBA in early lactation cows and the animals supplemented with calcium salts of fatty acids and calcium acetate shower higher levels of cholesterol in early lactation and the T3 group in the mid lactation.